Perbandingan Latihan Kekuatan Resistance Band dan Dumbbell terhadap Hasil Shooting Jarak 6 Meter Cabang Olahraga Petanque - Lambok Gabriel Oktavianus; Yasep Setiakarnawijaya; Dadan Resmana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine, 1) improvement in shooting technique through the resistance band training method, 2) improvement in shooting technique through the dumbbell training method, 3) calculation of improvement in shooting technique through the training method using resistance bands and dumbbells. The research method used in this research is an experiment with a quantitative approach and a Two Group Pretest Posttest Design research design. The subjects of this research were 30 Petanque athletes, students at SDN Rawamangun 09, taken using a purposive sampling technique. Data collection was carried out by conducting a shooting technique skills test at a distance of 6 meters using 1 target ball and 10 throws for each athlete. Data analysis was carried out using dependent and independent